Effects of High-Flux Dialysis Combined with Hemoperfusion on Serum GRP78 and miR-495-3p in Renal Failure Patients. (11th October 2021) - Fan, Wei; Li, Xudong; Xu, Xiangjun; Chu, Hong
Abstract : Objective . This study was designed to probe into the changes and clinical significance of GRP78 and miR-495-3p in renal failure (RF) patients during high-flux dialysis (HFD) combined with hemoperfusion (HP). Methods . Sixty-five RF patients and 74 health check-ups who were admitted in our hospital from March 2015 to February 2017 were prospectively selected, and the related characteristics were retrospectively collected for analysis. GRP78 and miR-495-3p were detected in RF patients at admission (before treatment), 12 weeks after treatment (during treatment), 24 weeks after treatment (after treatment), and the control group at admission, and the relationship between the two and the occurrence, efficacy, and recurrence of RF was analyzed. Results . Before treatment, the GRP78 mRNA level in RF patients was higher than that in health check-ups, while the miR-495-3p level was lower (P < 0.05 ). GRP78 mRNA in RF patients was lower than that before treatment and was the lowest after treatment. On the contrary, miR-495-3p was higher than that before treatment and was the highest after treatment (P < 0.05 ). The two had a significant effect on predicting RF before treatment, efficacy of patients, and their recurrence after treatment (all P < 0.001 ). Conclusion . GRP78 decreased during the treatment of high-flux hemodialysis (HF-HD) combined with systemic HP in RF patients, while miR-495-3p increased. Both of them have a good reference value for RF occurrence, treatment results, and recurrence.